Collaboration between paediatric surgery and other medical specialties in Nigeria - Philemon E Okoro; Emmanuel A Ameh (Wolters Kluwer Medknow Publications, 2012)
Background: The quality of service and success of patient care and research in most fields of medicine depend on effective collaboration between different specialties. Paediatric surgery is a relatively young specialty in Nigeria and such collaborations are desirable. This survey assesses the nature and extent of collaboration between paediatric surgery and other specialties in Nigeria. Materials and Methods: This is a questionnaire survey carried out in November 2008 among paediatric surgeons and their trainees practising in Nigeria. Questionnaires were distributed and retrieved either by hand or e-mailing. The responses were then collated and analysed using the SPSS 17.0. Results: Forty-seven respondents were included in the survey. Forty-five (95.7%) respondents thought that there was inadequate collaboration and that there was a need for an increased collaboration between paediatric surgery and other specialties. Anaesthesia, paediatrics and radiology are among the specialties where collaborations were most required but not adequately received. Collaboration had been required from these specialties in areas of patient care, training and research. Reasons for inadequate collaboration included the paucity of avenues for inter-specialty communication and exchange of ideas 33 (70.3%), lack of awareness of the need for collaboration 32 (68.1%), tendency to apportion blames for bad outcome 13 (27.7%), and mutual suspicion 8 (17%). Conclusion: There is presently inadequate collaboration between paediatric surgery and other specialties in Nigeria. There is a need for more inter-specialty support, communication, and exchange of ideas in order to achieve desirable outcomes.